2017
DOI: 10.3892/etm.2017.4198
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-type splenogonadal fusion: A case report

Abstract: Abstract. Splenogonadal fusion (SGF) is a rare congenital malformation. Since it lacks characteristic features, very few cases of SGF have been diagnosed preoperatively. Laparoscopy was effective in both diagnosing and surgically treating this condition. Herein, we reported left side SGF in a male patient who was diagnosed during laparoscopic exploration, and Fowler-Stephens orchidopexy was implemented at the same time. The patient was followed up for one year. At a 6-month follow-up, the left scrotum demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 11 publications
1
30
0
1
Order By: Relevance
“…If an aberrant fusion happens, during the gonadal descent (which starts at 8 th week) the splenic tissue would descend with the gonad and may be found anywhere along the normal descent path. [ 3 4 ] This theory also is consistent with the common association of limb and jaw defects with the continuous SGF because those mesenchymal derivatives (limb buds and Meckel's cartilage) also develop during the critical fusion time window.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…If an aberrant fusion happens, during the gonadal descent (which starts at 8 th week) the splenic tissue would descend with the gonad and may be found anywhere along the normal descent path. [ 3 4 ] This theory also is consistent with the common association of limb and jaw defects with the continuous SGF because those mesenchymal derivatives (limb buds and Meckel's cartilage) also develop during the critical fusion time window.…”
Section: Discussionsupporting
confidence: 72%
“…It has been reported that 25%–35% of SGF will necessitate orchiectomy because of testicular atrophy or inseparability of tissues. [ 3 4 ] This was the case for our patient where the testicular remnant was very much atrophied and later found to be of primitive histology. This was probably due to pressure applied on the testicular parenchyma by the splenic tissue enclosed within the unyielding tunica vaginalis.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…5,6 This entity is almost entirely left sided (98%) and demonstrates a profound male predominance (incidence ~ 16:1). 7 In 1956 Putschar and Manion classified SGF into two groups: continuous and discontinuous. In the continuous type, a cord of splenic tissue, a fibrous cord beaded with splenic nodules or a pure fibrous band anatomically connects the main spleen to the gonad.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that once an accurate pre-or intraoperative diagnosis is made, surgery is not needed in the absence of significant complications [17]. In patients with continuous SGF who undergo orchiopexy, the splenic band can be easily separated from the testicular vessels and removed alongside with the splenic tissue affecting the testis [18][19][20].…”
Section: Discussionmentioning
confidence: 99%